On One 2-Valued Transformation: Its Invariant Measure and Application to Masked Dynamical Systems - P. I. Troshin (Abstract and Applied Analysis)
We consider one family S of 2-valued transformations on the interval [0, 1] with measure μ, endowed with a set of weight functions. We construct invariant measure μS=μ for this multivalued dynamical system with weights and show the interplay between such systems and masked dynamical systems, which leads to image processing.